PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP PRESTASI KERJA KARYAWAN PABRIK GULA TJOEKIR - KRISMASARI, DINI (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract: This study aims to examine and analyze the effect of compensation and work discipline on employee performance part A.K.U. (Administration, Finance, and Public) in Tjoekir sugar factory in the district of Jombang. This study used 62 employees part A.K.U. (Administration, Finance, and Public) in sugar mills Tjoekir in Jombang district as the study sample. The data obtained were analyzed using regression analysis, to test the variable compensation and work discipline on employee performance. The results indicate a positive and significant effect of compensation and work discipline on employee performance part A.K.U (Administration, Finance, and Public) in Tjoekir sugar factory in the district of Jombang. Keywords : compensation , work discipline , employee performance.